Raw material management networks based on an improved P‐graph integrated carbon emission pinch analysis (CEPA‐P‐graph) method. (13th December 2019) - Mu, Peng; Yang, Yu; Han, YongMing; Gu, Xiangbai; Zhu, QunXiong
Abstract: Raw material management plays an essential role in the environment production and carbon emission problem. A P‐graph is an effective tool that can be used to solve the raw material management problem. However, raw material management based on the P‐graph is complicated and inaccurate. Therefore, this paper proposes an improved P‐graph integrating carbon emission pinch analysis (CEPA‐P‐graph) method to resolve raw material management problem with simpler structures and less results. The proposed method is applied in raw material planning in terms of the regional energy planning problem, and two ethylene plants under carbon emission constraints are examined. As the parameter information of the problem is utilized by pinch technology, the search domain of structure optimization is further reduced, and the computing complexity is reduced, while the advantages of the P‐graph multi‐solution are guaranteed. The experimental results demonstrate the validity of the proposed method. Furthermore, the CEPA‐P‐graph could reduce the complexity of solution structure generation by ~70% and reduce the carbon emission per unit product by 17%.